Symbolic representations in the Ivisanon supernatural tales. - Olisco, Mary Jane O.
This study identifies the spirit beings whose names are famous to the people of Ivisan. These spirit beings include Tutok, Marshal, Donya Mimay and Mamilpil. These spirit beings participate in the communal life of the people of Ivisan. Tutok is famous for being generous fo he allows people to borrow some kitchen wares for weddings and fiestas. Marshal is famous for owing a piece of cloth from a tagalog vendor. He is famous also for being the owner of the abounding wild boars in his territory. Donya Mimay is believed to be Mamilpil's wife. While Mamilpil is the captain of the gold boat which docks along the shoreline of Barangay Matnog. These spirit beings, however, represent the dominant class who dominate the power and wealth in their community as perceived by the Ivisanon.